Does a hypertrophying muscle fibre reprogramme its metabolism similar to a cancer cell? - Wackerhage, H.; Vechetti, I. J.; Baumert, P.; Gehlert, S.; Becker, L.; Jaspers, R. T.; de Angelis, M. H. (Sports Medicine, 2022)
In 1924, Otto Warburg asked "How does the metabolism of a growing tissue differ from that of a non-growing tissue?" Currently, we know that proliferating healthy and cancer cells reprogramme their metabolism. This typically includes increased glucose uptake, glycolytic flux and lactate synthesis. A key function of this reprogramming is to channel glycolytic intermediates and other metabolites into anabolic reactions such as nucleotide-RNA/DNA synthesis, amino acid-protein synthesis and the synthesis of, for example, acetyl and methyl groups for epigenetic modification. In this review, we discuss evidence that a hypertrophying muscle similarly takes up more glucose and reprogrammes its metabolism to channel energy metabolites into anabolic pathways. We specifically discuss the functions of the cancer-associated enzymes phosphoglycerate dehydrogenase and pyruvate kinase muscle 2 in skeletal muscle. In addition, we ask whether increased glucose uptake by a hypertrophying muscle explains why muscularity is often negatively associated with type 2 diabetes mellitus and obesity.